Quantidade de chuva e lixiviação do herbicida metribuzin através de planta bioindicadora - Silva Júnior, Antonio Carlos da [UNESP]; Queiroz, Juliana Roberta Gobi [UNESP]; Martins, Dagoberto [UNESP] (FapUNIFESP (SciELO), 2015)
The objective of this study was to evaluate the potential for leaching of the metribuzin herbicide under natural rain in two soils with contrasting textures, clay and medium sandy soil under field conditions using bioindicator plant. PVC columns were introduced in both soils maintaining the original integrity of the soil during the sampling that occurred after accumulation of precipitation stipulated in the interval in ambient, between 30-40, 60-80 and 100-120 mm of rain. The columns were separated by longitudinal section for the sowing of bioindicator plant (25 plants). After sowing, phytotoxicity evaluations of bioindicator plant were conducted at 5, 7, 10 and 12 days after sowing through a scale from 0 to 100%. The leaching of the herbicide metribuzin was dependent on the precipitation received in the two studied soil types. The effectiveness of the bioindicator plant depends on the type of soil and amount of precipitation. The method using bioindicator plant proved to be efficient for the evaluation of the mobility of herbicide in the soil profile.

Objetivou-se, neste trabalho, avaliar o potencial de lixiviação do herbicida metribuzin com precipitações pluviométricas naturais, em dois solos com texturas contrastantes, argiloso e médio arenoso, em condições de campo, através de planta bioindicadora. Colunas de PVC foram introduzidas nos dois solos. Manteve-se a integridade original do solo durante a coleta das amostras, que ocorreu após o acúmulo das precipitações em um intervalo estipulado ao ambiente entre 30-40, 60-80 e 100-120 mm de chuva. As colunas foram separadas com corte longitudinal para a semeadura da espécie bioindicadora (25 plantas). Após a semeadura avaliações de fitotoxicidade das plantas bioindicadoras foram realizadas aos 5, 7, 10 e 12 dias após a semeadura, através de uma escala de notas de 0 a 100%. A lixiviação do herbicida metribuzin foi dependente da precipitação recebida para os dois tipos de solo estudados. A eficácia da planta bioindicadora dependeu do tipo de solo e da precipitação. A metodologia de utilização de plantas bioindicadoras mostrou-se eficiente para avaliação da mobilidade de herbicida no perfil do solo.
Rain amount and leaching of the herbicide metribuzin through bioindicator plant
Keywords: Mobility; Dynamic; Cucumis sativus; Soil texture; Mobilidade; Dinâmica; Cucumis sativus; Textura do solo